The effect of pouring temperature on the porosity of sand casted Al – Si alloy. (March 2019) - Arif Irfa, Mochamad'i; Dzulkiflih,; Wulandari, Diah; N.F Ganda, Andita; Supardiyono,
Abstract: This study was conducted to know the effect of pouring temperature on the porosity of Al – Si alloy cast in the sand moulding. Al – Si alloy was melted using reverberator I. 706 furnace which was equipped with temperature controller. The liquefied Al – Si alloy was charged into the sand moulding with varied pouring temperature from 680°C, 705°C, 730°C, 755°C and 780°C. The riser model moulding was used in this research. The porosity measurement was done by calculating the specimen weight at the open air and in the fluid (density calculation). The measurement would give the value of actual and theoretical density. Dye penetrant method was also used for porosity measurement at outer part of tested specimen. The average porosity of the sand moulded Al – Si alloy with the varied pouring temperature are 4.31%, 4.05%, 3.85%, 2.98% and 2.81% respectively. The porosity analysis using dye penetrant method showed that the gas porosity was shifting out to the outer part of specimen. In addition, the amount of porosity in the outer part tend to increase and harvest in the one point with the increase of pouring temperature.